New mothers and social support: A mixed-method study of young mothers in Australia - Hoffmann, Heidi; Olson, Rebecca E.; Perales, Francisco; Baxter, Janeen (My University, 2020)
Motherhood can bring joy and enrichment but may also be associated with stress leading to poor health outcomes and low life satisfaction. Young mothers are a group particularly at risk of adverse outcomes, including increased social, economic, and health disadvantage following early entry to motherhood. This article reports results from a mixed-method study examining variations in levels of social support reported by mothers. Cross-sectional analyses of survey data from the Longitudinal Study of Australian Children showed that young mothers (aged less than 25 years when their child was born) generally reported higher levels of social support, but poorer family relationships than older mothers. In-depth interviews with nine young mothers provided insights into how they perceived support under these circumstances. Our research shows that young mothers often experienced difficult childhoods and strained relationships with parents, but many reconnected with their mothers after pregnancy and saw them as important sources of support.
Journal of Sociology
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Families and relationships; Social engagement